Are household food security, nutrient adequacy, and childhood nutrition clustered together? A cross-sectional study in Bankura, West Bengal - Satabdi Mitra; Dipta Kanti Mukhopadhyay; Aditya Prasad Sarkar; Indrajit Saha (Wolters Kluwer Medknow Publications, 2019)
Background: Research on different measures of food security and their interrelation in order to identify vulnerable households are scarce in India. Objectives: The objective was to assess household food security (HHFS), nutrient adequacy, dietary diversity, and nutritional status of under-five children along with their interrelation in the slums of Bankura Municipality, West Bengal. Methods: A cross-sectional study was conducted during 2016-2017 among 240 households using two-stage 30-cluster random sampling. Information regarding socioeconomic characteristics, availability, and utilization of different poverty alleviation schemes was collected. HHFS was assessed by a validated HHFS scale-short form in Bengali and nutrient adequacy with 24-h recall method. The eldest under-five child in the family was measured for anthropometry using standard procedure and for dietary diversity with the Individual Dietary Diversity Score. Results: Overall, 74 (29.1%) households had "food security," whereas 102 (44.3%) and 64 (26.6%) had, respectively, low and very low food security. Among 190 under-five children, 63 (35.3%) had single and 50 (25.5%) had multiple anthropometric failures. Overall, 89 (36.1%) households were deficient for both energy and protein and 111 (47.6%) had deficiency of either of these two. Indicators on the utilization of different poverty alleviation schemes were associated with low/very low food security. A "Composite Index of Food Scarcity" comprising of HHFS, nutrient adequacy, and dietary diversity was proposed which was found to have dose-response relationship with grades of anthropometric failure of under-five children. Conclusions: An index comprising of three indicators might help identify the vulnerable households in relation to food security more effectively than a single indicator.